2010
DOI: 10.4196/kjpp.2010.14.6.359
|View full text |Cite
|
Sign up to set email alerts
|

Sigma-1 Receptor Antagonist BD1047 Reduces Allodynia and Spinal ERK Phosphorylation Following Chronic Compression of Dorsal Root Ganglion in Rats

Abstract: Many therapeutic roles have been proposed for sigma-1 receptor (Sig-1R), but the involvement of Sig-1R in neuropathic pain has currently not been well explored. The present study aimed to evaluate the anti-nociceptive effect of Sig-1R antagonist (BD1047) in a rat model of chronic compression of the dorsal root ganglion (CCD), which is a model of human foraminal stenosis and radicular pain. W hen stainless steel rods were inserted into the intervertebral foramen of lumbar vertebrae 4 and 5, the CCD developed re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…Although SN79 treatment was found to mitigate METH-induced increases in STAT3 phosphorylation, it may be possible that modulation of ERK1/2 and JNK pathways are contributing to increases in SOCS3 (Baker et al 2008), thereby leading to the blockade of STAT3 phosphorylation seen in the current report. Supporting this hypothesis are previous studies showing the modulation of ERK1/2 and JNK signaling by various sigma receptor ligands (Cantarella et al 2007; Nishimura et al 2008; Son and Kwon 2010; Tan et al 2010; Tuerxun et al 2010), although their effects specifically within astrocytes on these signaling pathways are currently unknown.…”
Section: Discussionmentioning
confidence: 77%
“…Although SN79 treatment was found to mitigate METH-induced increases in STAT3 phosphorylation, it may be possible that modulation of ERK1/2 and JNK pathways are contributing to increases in SOCS3 (Baker et al 2008), thereby leading to the blockade of STAT3 phosphorylation seen in the current report. Supporting this hypothesis are previous studies showing the modulation of ERK1/2 and JNK signaling by various sigma receptor ligands (Cantarella et al 2007; Nishimura et al 2008; Son and Kwon 2010; Tan et al 2010; Tuerxun et al 2010), although their effects specifically within astrocytes on these signaling pathways are currently unknown.…”
Section: Discussionmentioning
confidence: 77%
“…It has been reported that p38 MAPK plays an important role in a variety of chronic pain states. 45,46,48) Especially, Li et al showed that the expression of c-Fos and pp38 MAPK in the spinal cord dorsal horn were increased after an injection of formalin into the paw. 49) Recent study from Tan et al also reported that the activation of the Src/p38 MAPK signaling cascade in spinal microglia contributed to late stage persistent mechanical hyperalgesia evoked by formalin injection into the paw.…”
Section: Discussionmentioning
confidence: 97%
“…44) In particular, phosphorylated ERK (pERK) and p38 (pp38) MAPK in the spinal cord dorsal horn cells plays an important role in the induction and maintenance of pain hypersensitivity caused by partial sciatic nerve injury. 9, [44][45][46] Recently, Son and Kwon revealed that both allodynia induction and spinal pERK elevation were completely prevented during the time of BD1047 treatment (0-5 d after chronic compression on the DRG). 47) Furthermore, the Sig-1R knockout mice did not show any increase of pERK in the spinal cord after sciatic nerve injury, 9) suggesting that Sig-1Rs might be related to the mechanism of induction of ERK activation in the neuropathic condition.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that σ 1 receptor antagonists reduce the pain responses in the second phase of the formalin test, 23,25,27 the mechanical hypersensitivity induced by capsaicin, 22,24,27 and the neuropathic pain responses in various models. [27][28][29] There is an apparent discrepancy between the normal occurrence of capsaicin-induced referred hyperalgesia in σ 1 -KO mice and the inhibition of this hyperalgesia in WT mice treated with σ 1 receptor antagonists. This mismatch may be attributable to the development of compensatory mechanisms in σ 1 -KO mice versus WT animals, a general fact in genetic knockout experiments.…”
Section: Discussionmentioning
confidence: 99%